Explanatory abstractions - Jansson, Lina; Juha, Saatsi (Oxford University Press, 2019)
A number of philosophers have recently suggested that some abstract, plausibly non-causal and/or mathematical, explanations explain in a way that is radically different from the way causal explanation explain. Namely, while causal explanations explain by providing information about causal dependence, allegedly some abstract explanations explain in a way tied to the independence of the explanandum from the microdetails, or causal laws, for example. We oppose this recent trend to regard abstractions as explanatory in some sui generis way, and argue that a prominent account of causal explanation can be naturally extended to capture explanations that radically abstract away from microphysical and causal nomogical details. To this end, we distinguish different senses in which an explanation can be more or less abstract, and analyse the connection between explanations’ abstractness and their explanatory power. According to our analysis abstract explanations have much in common with counterfactual causal explanations.